Dietary magnesium intake affects the association between dietary vitamin A and depression: a cross-sectional study - Yan, Canqun; Gao, Conghui; Zhan, Kebin; Li, Cheng (Frontiers in Nutrition, 2025)
IntroductionDepression represents a significant global health burden, ranking as one of the leading causes of disability worldwide, and nutrition plays a key role in mental health. Vitamin A, essential for immune and neurological function, has shown conflicting associations with depression. Magnesium, essential for neurotransmission and neuroprotection, is associated with a reduced risk of depression. Importantly, magnesium is required for the activation of enzymes involved in vitamin A metabolism, suggesting a potential interaction between these nutrients in depression. However, this interaction remains poorly understood. This study investigates how magnesium intake modifies the relationship between vitamin A and depression, with the aim of elucidating their combined effects and informing personalized dietary strategies for depression prevention.Research design and methodsData for this study were extracted from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2016, involving a total of 60,936 participants. The final analysis included 25,277 adults aged ≥20 years (Female: 12,581, Male:12,696), excluding pregnant women, individuals under 20, and those with incomplete data. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9), supplemented by self-reporting questionnaires. Dietary intake was assessed via a recall interview at the mobile examination center (MEC). Dietary vitamin A intake, treated as a continuous variable, was categorized based on the median intake value. Stratified analyses were conducted based on sex and magnesium intake levels (Female: low: <310 mg/day; high: ≥310 mg/day; Male: low: <400 mg/day; high: ≥400 mg/day).ResultsOur cross-sectional study showed that in women with low magnesium intake, higher vitamin A intake was associated with a reduced risk of depression (OR: 0.83, 95% CI: 0.76–0.92, p < 0.001), whereas no significant association was observed in the high magnesium group. Men did not show such an interaction. There was also a significant interaction between vitamin A levels and magnesium intake in reducing the incidence of depression (p-value for interaction = 0.145).ConclusionOur study suggests that a sex-specific interaction between dietary magnesium and vitamin A in modulating depression risk. This interaction highlights the potential role of combined nutritional interventions in depression management. Further randomized controlled trials are warranted to confirm these findings.